Her last affair : [large type] a novel - Searles, John (Harper Large Print, an imprint of HarperCollinsPublishers, 2022)
"Skyla lives alone in the shadow of the defunct drive-in movie theater that she and her husband ran for nearly fifty years. Ever since Hollis's death in a freak accident the year before, Skyla spends her nights ruminating about the regrets and deceptions in her long marriage. That is, until she rents a cottage on the property to a charming British man, Teddy Cornwell.... A thousand miles away, Linelle is about to turn fifty. Bored by her spouse and fired from her job when a questionable photo from her youth surfaces on social media, her only source of joy is an on-line affair with her very first love, a man she's not seen in nearly thirty years, Teddy Cornwell... While in New York City, Jeremy, a failed and bitter writer, accepts an assignment to review a new restaurant in Providence. Years ago, Providence was the site of his first great love and first great heartbreak--and maybe, just maybe, he'll look her up when he's back in town..."--